Síndrome de prolapso de mucosa rectal: estudio de casos. Hospital Daniel A Carrión,Lima, Perú. 2010-2013 - Arévalo Suarez, Fernando (2014)
Objective: to describe the clinical, endoscopic, and histological characteristics of rectal mucosal prolapse syndrome, formerly known as Solitary rectal ulcer, in patients from a general hospital. Material and methods: All patient diagnosed as rectal mucosal prolapse syndrome during 2010-2013 was selected; the medical history war reviewed and the histological slides were reevaluated by two pathologists. Results: 17 cases of rectal mucosal prolapse syndrome were selected, the majority were males under 50 years, the most common clinical findings were rectal bleeding (82%) and constipation (65%), the endocopic findings were heterogeneous,: erythema (41%), ulcers (35%) and elevated lesions (29%). All cases presented fibromuscular hyperplasia in lamina propia and crypt distortion in the microscopic evaluation. Conclusion: In our study of rectal mucosal prolapse syndrome. The most common clinical findings were rectal bleeding and constipation. Erythematous mucosa was the most common endoscopic finding.